Contraindications to Whole-Body Cryostimulation (WBC). A position paper from the WBC Working Group of the International Institute of Refrigeration and the multidisciplinary expert panel - Capodaglio, Paolo; Alito, Angelo; Duguè, Benoit Michel; Bouzigon, Romain; Lombardi, Giovanni; Miller, Elzbieta Dorota; Verme, Federica; Modaffari, Giuseppe; Piterà, Paolo; Ziemann, Ewa; Fontana, Jacopo Maria (Frontiers in Rehabilitation Sciences, 2025)
BackgroundWhole-Body Cryostimulation (WBC) is a treatment that involves short exposures of the entire body to very cold and dry air in specially adapted cryochambers. A growing body of literature suggests the safe application of this technique in medical settings.AimThe primary purpose of this study was to generate an international consensus on the updated contraindications for WBC through an interactive process of questionnaire interspersed with controlled feedback from a steering committee.DesignThe study design was based on a systematic review of the literature and Delphi methodology.SettingAdministration of electronic online questionnaires concerning contraindications to WBC.PopulationA multidisciplinary panel of 48 experts in the fields of rehabilitation, cardiology, neurology, endocrinology, oncology, clinical nutrition or in the clinical application of WBC was invited to participate in this consensus study.MethodsA systematic search of PubMed, Scopus and Embase databases was carried out to identify possible items for inclusion in a form. A two-round Delphi survey was then conducted according to international guidelines, consisting of an electronic online questionnaire. The experts had to rate their agreement with each item in the questionnaires on a 5-point Likert scale. Expert consensus was assessed.ResultsA total of 28 European experts participated in the Delphi survey. The first round consisted of 59 items, 3 of which were discarded after data analysis. The second round was rearranged according to the previous suggestions of the panellists. All 28 experts completed the two rounds. At the end of the survey, consensus was reached and a final list of temporal and absolute contraindications to WBC was identified.ConclusionsThis process resulted in multidisciplinary expert consensus statements on contraindications to WBC. The European experts agreed on most of the decisions and produced a list of contraindications.Clinical rehabilitation impactThe results provide a robust evidence framework to help clinicians improve clinical practice and patient safety.